Competitive dynamics of air transport in Brazil: 2008-2014 - Abel, Luiz Fernando (2016)
Commercial aviation in Brazil has been facing great changes in the past years, from the regulatory point of view to a competition perspective, given the increase in demand, revision of past legislation and the rise of new players in this market. The airline business has showed to be very dynamic in Brazil, with the rise and fall of a number of companies. One of them specifically, called VARIG – Portuguese acronym for Viação Aérea Rio-Grandense -, which stopped operating domestic and international routes in 2006, changed the market significantly, since it was the longest standing air company in the country and also the market leader. This scenario of disruption, after VARIG’s bankruptcy, gave room to the consolidation of other major companies already operating at that time – TAM and Gol -, as well as the emergence of Avianca Brazil and Azul, which absorbed part of the increasing demand for air transport in the country and placed this market into a new era of competition. All these factors combined with the flexibility given, due to revision of legislation - referring to prices and alliances, for example -, have transformed the way business in the industry are run. Hence the changes in the way air companies operate nowadays and provide different types of services. Thus, the purpose of this work is to understand what are the competitive advantages of the Brazilian airline companies to face the local competition, given the changes between 2008 and 2014 in this sector’s environment. In addition, this work aims to identify competitive changes with possible new entrants to this market in the future.